2012
DOI: 10.1111/j.1365-2184.2012.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Jagged‐1‐mediated activation of notch signalling induces adipogenesis of adipose‐derived stem cells

Abstract: The results led to the conclusion that activation of Notch signalling had stimulated adipogenesis of mASCs in the presence of adipogenic medium by promoting expression of PPAR-γ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…Although we did not prove the form of the recombinant mouse Jagged1 protein used in this study, the increase in Hes1 and Hey1 both at protein and gene levels and the use of DAPT may explain the Jagged1 used in this study was an activator not an inhibitor. And our lab previous study also showed the recombinant Jagged1 used in this study was an activator (Ba, ) and the same results were also showed by other groups (Buchler, ; Bing, ).…”
Section: Discussionsupporting
confidence: 88%
“…Although we did not prove the form of the recombinant mouse Jagged1 protein used in this study, the increase in Hes1 and Hey1 both at protein and gene levels and the use of DAPT may explain the Jagged1 used in this study was an activator not an inhibitor. And our lab previous study also showed the recombinant Jagged1 used in this study was an activator (Ba, ) and the same results were also showed by other groups (Buchler, ; Bing, ).…”
Section: Discussionsupporting
confidence: 88%
“…2B,C). We then confirmed the effect of Notch inhibition by silencing the expression of JAG1, a crucial ligand for Notch signaling that induces cell differentiation (Ba et al, 2012), and which was significantly upregulated in pNCCs (Fig. 1H).…”
Section: Derivation Of Pnccs From Hescssupporting
confidence: 57%
“…3A, B). We used Oil Red O, which stains neutral triglycerides and lipids, and immunocytochemistry to look for the expression of perilipin, an essential protein for lipid storage and lipolysis [27] located exclusively on adipocyte lipid droplets [34]. Consistent with our results on PDGFRa expression, only type-1 pericytes differentiated into adipocytes in culture.…”
Section: Type-1 But Not Type-2 Pericytes Express the Adipogenic Progesupporting
confidence: 55%